تطبيق التعلم القائم على المشاريع في تعليم مهارة الكتابة لدى طلاب قسم اللغة اللغة العربية وآدابها في جامعة ماجيني - Mahyaddin, Fikriyah; Widodo, Arif (Yayasan Mutiara Hati Moeslem, 2025)
This study aims to describe the implementation of a project-based learning model in teaching Arabic writing skills to students in the Arabic Language and Literature Study Program at the State Islamic College of Majene. Arabic writing skills, as one of the fundamental skills in Arabic language learning, requires creative and applicable instructional strategies. The project-based learning model was selected because it promotes an active, collaborative learning process centered on real-life projects that are relevant to students’ experiences. This research employed a descriptive qualitative approach, with data collected through observations, interviews, and documentation of student projects. The findings indicate that the implementation of project-based learning significantly enhanced students’ motivation, engagement, and writing proficiency. Students showed notable improvements in writing structure, grammatical accuracy, and creativity in content development. In addition, this model also fostered critical thinking and collaborative skills. Therefore, project-based learning can serve as an effective alternative approach for teaching Arabic writing skills in other higher education institutions